Trends in prevalence of hypertension in Argentina in the last 25 years: a systematic review of observational studies - Alejandro Díaz; Daniel Ferrante
OBJECTIVE:To estimate the pooled prevalence of hypertension in Argentina and analyze the trends in the level of hypertension awareness, treatment, and control in the period 1988-2013. METHODS: A bibliographic search was conducted in MEDLINE, SciELO, and LILACS databases for studies on hypertension prevalence conducted from 1988 to 2013. Eligibility criteria for inclusion were as follows: 1) population-based cross-sectional studies and surveys with blood pressure (BP) measurements in which prevalence of hypertension (or data to calculate it) was reported; 2) population-based studies conducted in adults from Argentina (people > 18 years old); and 3) studies in which the hypertension condition was defined as average systolic BP > 140 mmHg or diastolic BP > 90 mmHg or as use of antihypertensive medications. RESULTS: Twenty peer-reviewed publications were identified that reported the prevalence of hypertension for a collective total of 33 397 patients. The crude hypertension prevalence reported for Argentina was 32.34% (95% CI: 30.0-34.1). The prevalence of hypertension in people > 65 years old was > 71%. Only nine studies assessed the level of hypertension awareness, treatment, and control (57.9%, 49.5%, and 20.5% respectively). The most prevalent cardiovascular risk factor was sedentary habits (54.4%), central (abdominal) obesity (47%), overweight (43.1%), dyslipidemia (34.7%), smoking (27.4%), and diabetes (5.3%). CONCLUSIONS: Hypertension is of public health importance in Argentina, with evidence of considerable under-diagnosis and insufficient treatment and control. There is an urgent need to develop strategies to prevent, detect, treat, and control hypertension effectively countrywide.